2015
DOI: 10.1007/978-3-319-16555-4_3
|View full text |Cite
|
Sign up to set email alerts
|

Theranostic Magnetic Nanostructures (MNS) for Cancer

Abstract: Despite the complexities of cancer, remarkable diagnostic and therapeutic advances have been made during the past decade, which include improved genetic, molecular, and nanoscale understanding of the disease. Physical science and engineering, and nanotechnology in particular, have contributed to these developments through out-of-the-box ideas and initiatives from perspectives that are far removed from classical biological and medicinal aspects of cancer. Nanostructures, in particular, are being effectively uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 172 publications
(226 reference statements)
1
29
0
Order By: Relevance
“…Sensitivity and specificity of cancer detection by MRI using nontargeted or targeted IONPs have been demonstrated in experimental animals as well as in human patients [32][33][34]. Results of those studies showed that core size, shape, surface property and functionalization of IONPs affect in vivo biodistribution, blood half-life, stability, pharmacokinetics, targeted delivery and MRI contrast intensity.…”
Section: Physical and Chemical Characteristics Of Ionpsmentioning
confidence: 99%
“…Sensitivity and specificity of cancer detection by MRI using nontargeted or targeted IONPs have been demonstrated in experimental animals as well as in human patients [32][33][34]. Results of those studies showed that core size, shape, surface property and functionalization of IONPs affect in vivo biodistribution, blood half-life, stability, pharmacokinetics, targeted delivery and MRI contrast intensity.…”
Section: Physical and Chemical Characteristics Of Ionpsmentioning
confidence: 99%
“…There are numerous reports of Gd(III)–nanoparticle formulations with high cell labeling efficiency and imaging efficacy. 1,2,5,10,2023 In particular, carbon-based nanomaterials bearing Gd(III) ions such as gadographene, gadofullerene, and gadonanotubes have been explored. 21,2427 However, a majority of these constructs have not enabled long-term cell labeling and fate mapping in vivo due to limited stability in biological media.…”
Section: Introductionmentioning
confidence: 99%
“…However, Cellax ™ (a covalently conjugated Dtxl onto polyethylene glycol-acetylated carboxymethylcellulose to form self-assembled 120 nm particles) [1214] and BIND-014 (Dtxl encapsulated in biodegradable polymer based nanoparticles) [15, 16] are emerging as clinically useful nanoformulations. Among various nanoparticle based drug nanoformulations, superparamagnetic iron oxide nanoparticles (SPION) or magnetic nanoparticles (MNPs) have recently received considerable attention as theranostic applications [therapy (drug delivery, hyperthermia) and diagnosis (MR imaging, tumor cell-isolation)] due to their biocompatibility and superparamagnetic properties [1720]. Therefore, formulation of docetaxel with SPION would not only enhance its biological activity but also add imaging capability to the treatment modality.…”
Section: Introductionmentioning
confidence: 99%